PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN NET PROFIT MARGIN (NPM) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 -2019 - Nur Melinda Hastuti; Hj. Siti Rusidah; Setio Utomo (Smart Business Journal, 2021)
The object of this study is the banks that are listed on the Indonesia Stock Exchange for the period 2015-2019. The banking sector was chosen because it is very instrumental in advancing a country's economy. Because almost all sectors of the economy are related to financial activities that will require the role of banks. To measure the success of a bank, it can be seen from the profit growth of a bank. This study aims to determine the effect of Return on Assets (ROA) (X1), Return On Equity (ROE) (X2), and Net Profit Margin (NPM) (X3) on Profit Growth (Y) in Banking Companies listed on the Stock Exchange Indonesia Period 2015-2019. The data used in this study are secondary data in the form of published financial statements. The sample used was 22 companies multiplied by 5 years of the study period with purposive sampling technique. Data analysis method used is Multiple Linear Regression Analysis. The results prove that Return On Assets (ROA) partially does not significantly influence profit growth of -14.2%, Return On Equity (ROE) partially does not significantly influence profit growth of 9.1%, and Net Profit Margin (NPM) partially significant effect on profit growth of 51%. Simultaneously Return on Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) have a significant effect on Profit Growth with a contribution of 19.4% which shows very low. Keywords: Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Growth Profit.